2007
DOI: 10.1016/j.acra.2006.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Localization Accuracy of Radiologists in Free-Response Studies: Inferring Perceptual FROC Curves from Mark-Rating Data

Abstract: Free-response data consists of a set of mark-ratings pairs. Prior to analysis the data is classified or "scored" into lesion and non-lesion localizations. The scoring is done by choosing an acceptanceradius and classifying marks within the acceptance-radius of lesion centers as lesion localizations, and all other marks are classified as non-lesion localizations. The scored data is plotted as a freeresponse receiver operating characteristic (FROC) curve, essentially a plot of appropriately normalized numbers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 32 publications
1
19
0
1
Order By: Relevance
“…The analysis was performed using JAFROC1 analysis software version 1.0 (http:// devchakraborty.com/) [19]; figure-of-merit values representing the diagnostic accuracy were compared in the non-enhanced and the gadoxetic acid-enhanced image sets for both T 2 weighted and DW imaging using the F-test. To evaluate the effect of gadoxetic acid enhancement on lesion characterisation, we identified focal hepatic lesions that were detected on both nonenhanced and gadoxetic acid-enhanced images by each of the two readers.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis was performed using JAFROC1 analysis software version 1.0 (http:// devchakraborty.com/) [19]; figure-of-merit values representing the diagnostic accuracy were compared in the non-enhanced and the gadoxetic acid-enhanced image sets for both T 2 weighted and DW imaging using the F-test. To evaluate the effect of gadoxetic acid enhancement on lesion characterisation, we identified focal hepatic lesions that were detected on both nonenhanced and gadoxetic acid-enhanced images by each of the two readers.…”
Section: Discussionmentioning
confidence: 99%
“…Harisinghani et al [17], studying digital workstation ergonomics, have suggested that the distance from the observer to the screen should be at least 25 inches (63.5 cm) [17]. Other approaches to scoring that do not rely on an acceptance radius include using statistical methods to classify ''perceptual hits'' and ''perceptual misses'' [9] or asking readers to outline a lesion [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…If the mark falls within the circle whose centre corresponds to the centre of the lesion as predetermined by the investigator and whose radius is the acceptance radius (the acceptance circle), the mark is scored as an LL. Any mark outside of the acceptance circle is scored as an NLL [9]. The purpose of this study was to evaluate the effects of varying the acceptance radius for a nodule detection task in chest radiography in order to suggest guidelines for determining the acceptance radius.…”
mentioning
confidence: 99%
“…Acceptance regions of lesions are varied in peer review literature, this study has followed the Chakraboty 34 recommendation of a maximum diameter of a lesion or 3 mm. Acceptance radiuses are a controversial topic in observer performance studies and Chakraborty 34,35 considers the question of what is the maximum inaccuracy with no clinical impact that would be acceptable in a study scenario.…”
Section: Methodsmentioning
confidence: 99%